Analisis Yuridis Penerapan Regulasi Isbat Nikah Poligami di Pengadilan Agama Sibuhuan Perkara Nomor 90/Pdt.P/2023/PA.Sbh dan Nomor 217/Pdt.P/2022/PA.Sbh dalam Perspektif Keadilan - Muhammad Yusuf Nasution; Muhammad Arsad Nasution; Putra Halomoan Hasibuan (TERAJU: Jurnal Syariah dan Hukum, 2025)
This research examines the following instances from a justice standpoint: The procedure that the Sibuhuan Religious Court follows in situations concerning polygamous marriages is outlined in Articles 90/Pdt.P/2023/PA.Sbh and 217/Pdt.P/2022/PA.Sbh: 1) What are the procedures for carrying out the rulings of the Sibuhuan Religious Court regarding polygamous marriages? 2) The cases of 90/pdt.p/2023 PA.Sbh and 217/Pdt.P/2022/PA.Sbh include polygamous marriage; what was the judge's decision on this matter? How did the court arrive at its decision? What factors and cases were considered? Sources consulted included the 1974 Marriage Law, Islamic legal treatises, Supreme Court circulars, judgements made by religious courts, publications, journals, and prior study on family law fiqh, as well as other primary and secondary sources. In line with SEMA No. 3 of 2018, the Sibuhuan Religious Court approved the marriage based on these findings. Problems have arisen as a result of court rulings in cases 90/Pdt.P/2023/PA.Sbh and 217/Pdt.P/2022/PA.Sbh, which suggest legal smuggling connected to the certification of polygamous marriages. There is variability in the way the judges take legal factors into account.